Solid waste management need & implementation in Raipur, Chhattisgarh - Lanjewar, Sandhya S; Sharma, Kavita; Mahishwar, Anita (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The municipal government is generally the agency responsible for implementing municipal solid waste management programs and facilities, proactive communities often take an active role in solid waste management planning. Integrated Solid Waste Management (ISWM) is a comprehensive waste prevention, recycling, composting, and disposal program. An effective Integrated Solid Waste Management system considers how to prevent, recycle, and manage solid waste in ways that most effectively protect health and the environment. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->